A Critical Appraisal of the Correspondence between Students' Attitudes towards the Use of Corrective Feedback Strategies and How They Are Implemented by Teachers in EFL Classroom Interactions. (31st March 2022) - Shahidzade, Farangis; Razmi, Mohammad Hasan; Tilwani, Shouket Ahmad
Abstract : As a critical appraisal, this study investigated the correspondence between teachers' corrective feedback strategies used in English as a foreign language (EFL) classes and students' preferences of corrective feedback strategies by analyzing both quantitative and qualitative data. The participants were 20 high school English teachers and 50 students of Salami High school in Kazeroun. To critically compare their preferences, both the students and teachers were asked to answer approximately identical questionnaires. The CF strategies were ranked according to the students' and teachers' attitudes. The results of the quantitative data analysis were as follows: There was no overall significant difference in CF preference of the students and CF usage of the teachers. The CF strategies were ranked by the teachers as teachers' elicitation followed by clarification request, repetition, recasting, and explicit correction in order. The students' preferences were ranked differently. Clarification request was the most preferred one followed by teacher's elicitation, repetition, recasting, and explicit correction in order. The qualitative results indicated that there were different individual justifications for their choices. This study concludes with some pedagogical implications and further suggestions for more research of corrective feedback strategies in different socio-cultural conditions.